Far Right Partisanship and Confidence in the United Nations and European Union Across the Nordic Countries - Hansen, Michael A; Kronlund, Anna; Immonen, Waltteri (Wiley, 2025)
Research finds a link between far‐right political partisanship and attitudes towards transnational institutions among European citizens—mainly in relation to the European Union (EU). Citizens that support far‐right parties tend to view the European Union as unjustly subverting national sovereignty, which leads to a higher level of Euroskepticism when compared to sup- porters of most mainstream parties. In this study, our contribution is that we explore whether the negative attitudes far‐right party supporters have towards the European Union extend towards the United Nations (UN). We utilize the joint Wave 5 European Values Study (EVS)/World Values Survey (WVS) Wave 7 to estimate multiple regression models predicting confi- dence in the EU and UN across the Nordic countries. The results confirm previous studies showing that confidence in the EU is lower among far‐right partisans. In addition, the results demonstrate that although smaller in size, there are many instances where far‐right partisans also have less confidence in the UN. The analysis shows that far‐right partisans' lack of confidence in supranational organizations also extends to transnational institutions, which is an important area of inquiry given the UN's role in mitigating current global crises.